Endosperm balance number manipulation for direct in vivo germplasm introgression to potato from a sexually isolated relative (Solanum commersonii Dun.) - Carputo, Domenico (The National Academy of Sciences of the USA, 1997)
Diploid (2n = 2x = 24) Solanum species with endosperm balance number (EBN) = 1 are sexually isolated from diploid 2EBN species and both tetraploid (2n = 4x = 48, 4EBN) and haploid (2n = 2x = 24, 2EBN) S. tuberosum Group Tuberosum. To sexually overcome these crossing barriers in the diploid species S. commersonii (1EBN), the manipulation of the EBN was accomplished by scaling up and down ploidy levels. Triploid F(1) hybrids between an in vitro-doubled clone of S. commersonii (2n = 4x = 48, 2EBN) and diploid 2EBN clones were successfully used in 3x × 4x crosses with S. tuberosum Group Tuberosum, resulting in pentaploid/near pentaploid BC(1) progenies. This provided evidence of 2n (3x) egg formation in the triploid female parents. Two selected BC(1) pentaploid hybrids were successfully backcrossed both as male and as female parents with S. tuberosum Group Tuberosum. The somatic chromosome number varied greatly among the resulting BC(2) progenies, which included hyperaneuploids, but also a number (4.8%) of 48-chromosome plants. The introgression of S. commersonii genomes was confirmed by the presence of S. commersonii-specific randomly amplified polymorphic DNA markers in the BC(2) population analyzed. The results clearly demonstrate the feasibility of germplasm introgression from sexually isolated diploid 1EBN species into the 4x (4EBN) gene pool of the cultivated potato using sexual hybridization. Based on the amount and type of genetic variation generated, cumbersomeness, general applicability, costs, and other factors, it would be interesting to compare the approach reported here with other in vitro or in vivo, direct or indirect, approaches previously reported.